Pengaruh abdominal stretching exercise terhadap intensitas nyeri haid pada remaja putri - Zari, Fidya Nata; Oktavia, Santi; Yuliana, Dewi (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Menstrual pain is a common problem often experienced by adolescent girls and can interfere with daily activities. One non-pharmacological method that can be used to reduce menstrual pain is abdominal stretching exercise, which functions to improve blood circulation, stimulate endorphin production, and reduce muscle tension. Purpose. Purpose: To determine the effect of abdominal stretching exercise on the intensity of menstrual pain in adolescent girls. Method: This quantitative research used a pre-experimental design with a one-group pretest-posttest design. The sample in this study was 42 eleventh-grade female adolescents experiencing menstrual pain, selected using a purposive sampling technique based on predetermined inclusion criteria. Pain intensity was measured using the NRS (Numerical Rating Scale) before and after abdominal stretching exercise intervention. Statistical tests were performed using the Wilcoxon Signed Rank Test. Result: The study showed that the average pain score before the intervention was 5.76 and after the intervention was 3.02. The Wilcoxon Signed Rank Test resulted in a p-value of 0.000 (<0.05). Therefore, the alternative hypothesis was accepted and the null hypothesis was rejected. Conclusion: Abdominal stretching exercises have been shown to affect the intensity of menstrual pain in adolescent girls. Based on these results, abdominal stretching exercises are recommended as a non-pharmacological intervention to address discomfort caused by menstrual pain. Keywords : Adolescent Girls; Abdominal Stretching Exercise; Menstrual Pain. Pendahuluan: Nyeri haid merupakan masalah umum yang sering dialami remaja putri dan dapat mengganggu aktivitas sehari-hari. Salah satu metode non-farmakologis yang bisa digunakan untuk mengurangi nyeri haid adalah latihan abdominal stretching exercise, yang berfungsi untuk memperlancar sirkulasi darah, memicu produksi endorfin, dan menurunkan ketegangan otot. Tujuan: Untuk mengetahui pengaruh abdominal stretching exercise terhadap intensitas nyeri haid pada remaja putri. Metode: Penelitian kuantitatif yang menggunakan desain Pre-Eksperimental dengan rancangan One Group Pretest-Posttest Design. Sampel dalam penelitian merupakan remaja putri kelas XI yang mengalami nyeri haid berjumlah 42 partisipan, dipilih menggunakan teknik purposive sampling berdasarkan kriteria inklusi yang telah ditetapkan. Pengukuran intensitas nyeri menggunakan NRS (Numeric Rating Scale), dilakukan sebelum dan setelah diberikan intervensi abdominal stretching exercise. Uji statistik dilakukan dengan menggunakan uji Wilcoxon Signed Rank Test. Hasil: Penelitian menunjukkan bahwa nilai rata-rata sebelum perlakuan 5,76 dan setelah perlakuan 3.02. Dari hasil uji Wilcoxon Signed Rank Test diperoleh hasil p-value = 0.000 (<0.05). Sehingga Ha diterima dan Ho ditolak. Simpulan: Ada pengaruh abdominal stretching exercise terhadap intensitas nyeri haid pada remaja putri. Berdasarkan hasil tersebut, abdominal stretching exercise direkomendasikan sebagai intervensi non-farmakologis untuk mengatasi gangguan rasa nyaman yang diakibatkan dari nyeri haid. Kata kunci : Abdominal Stretching Exercise; Nyeri Haid; Remaja Putri.